2010
DOI: 10.1177/0022034510384622
|View full text |Cite
|
Sign up to set email alerts
|

Potential of the Tannerella forsythia S-layer to Delay the Immune Response

Abstract: The periodontal pathogen Tannerella forsythia possesses a glycosylated S-layer as an outermost cell decoration. While the S-layer provides a selection advantage to the bacterium in the natural habitat, its virulence potential remains to be investigated. In the present study, the immune responses of human macrophages and gingival fibroblasts upon stimulation with wild-type T. forsythia and an S-layer-deficient mutant were investigated. The mRNA expression levels of the pro-inflammatory mediators IL-1β, TNF-α, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
97
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(105 citation statements)
references
References 35 publications
8
97
0
Order By: Relevance
“…Bacterial Strains, Medium, and Culture Conditions-T. forsythia wild-type strain ATCC 43037 (American Type Culture Collection) and defined mutants thereof were grown anaerobically for 4 -7 days in enriched tryptic soy broth as described previously (14). The S-layer gene mutants T. forsythia ⌬tfsA and ⌬tfsB, respectively (13), were kindly provided by Yukitaka Murakami (Aichi-Gakuin University, Nagoya, Japan), and the T. forsythia wecC mutant (6) was obtained from Ashu Sharma (State University of New York at Buffalo).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial Strains, Medium, and Culture Conditions-T. forsythia wild-type strain ATCC 43037 (American Type Culture Collection) and defined mutants thereof were grown anaerobically for 4 -7 days in enriched tryptic soy broth as described previously (14). The S-layer gene mutants T. forsythia ⌬tfsA and ⌬tfsB, respectively (13), were kindly provided by Yukitaka Murakami (Aichi-Gakuin University, Nagoya, Japan), and the T. forsythia wecC mutant (6) was obtained from Ashu Sharma (State University of New York at Buffalo).…”
Section: Methodsmentioning
confidence: 99%
“…This mutant induced significantly higher levels of the proinflammatory mediators IL-1␤, TNF-␣, and IL-8 compared with WT cells, especially at the early phase of response. This suggests that the S-layer attenuates the host immune response to this pathogen by evading its recognition by the innate immune system (14).…”
mentioning
confidence: 99%
“…The oligosaccharide modifying the glycoproteins of T. forsythia contains mannose, L-fucose, and Pse residues and is the result of genes in a 6-to 8-kb conserved locus (TF2049 to TF2055) (499). The S-layer of T. forsythia was identified as being an important virulence factor, as it helps the pathogen evade recognition by the innate immune system of the host (504,505).…”
Section: Protein Glycosylationmentioning
confidence: 99%
“…Also, TfsA and TfsB may mediate adhesion to, and/or invasion of, human gingival epithelial cells and epidermal carcinoma cells of the mouth and are associated with hemagglutination (11,23). Sekot et al have demonstrated that T. forsythia lacking the S-layer induces significantly higher levels of proinflammatory cytokines than WT T. forsythia (26), which suggests that the S-layer attenuates the host immune response by evading innate immune recognition.…”
mentioning
confidence: 99%